Entre a cruz e a espada: do excessivo controle judicial da administração pública à deferência judicial redimida - Santos, Mateus Levi Fontes (2022)
The goal of the dissertation is to justify and offer parameters for judicial deference to administrative action in Brazil. The method used is the hypothetical-deductive one. The problem that guides the research is whether, in the light of the Brazilian legal system, judicial deference, in the north american strand, can be used as a limit to the broad judicial review of the performance of brazilian public administration in its current context. The hypothesis is affirmative, since a parameterized judicial deference, inspired by Chevron and Auer cases, is a constitutional and legal attitude, that brings better consequences to the legal system. The institutionalism of Adrian Vermeule and Cass Sunstein theoretically justifies the proposed judicial deference. Art. 22 of the new Introduction Legal Act to the Norms of Brazilian Law (LINDB) is the specific legal basis for judicial deference in Brazil. Thus, inspired by Chevron and Auer cases, a model of judicial deference applicable to Brazil is proposed. Constitutional objections to this model are unconvincing. The operationalization difficulties are surmountable and equalized by the likely advantages that its adoption will bring to citizens, public administration and judiciary. Finally, the adoption of the proposed model of deference will not increase the risk of arbitrariness in detriment of citizens, once adopted the redeemed judicial deference. According to this approach – based on the idea of morality of administrative law, proposed by Sunstein and Vermeule and grounded on the doctrine of Lon Fuller – judicial deference involves counterparts from the administration. These charges, specifically provided for in the new LINDB, set safeguards for citizens and limit arbitrariness. Such an approach suggests a change in the profile of judicial review of the public administration – from substantive review of specific solution to procedural and deferential review of reasonable choice.